The relation and transformation between hierarchical inner product encryption and spatial encryption - Chen, Jie (2014)
Hierarchical inner product encryption (HIPE) and spatial encryption (SE) are two important classes of functional encryption that have numerous applications. Although HIPE and SE both involve some notion of linear algebra, the former works in vectors while the latter is based on (affine) spaces. Moreover, they currently possess different properties in terms of security, anonymity (payload/attribute-hiding) and ciphertext sizes, for example. In this paper, we formally study the relation between HIPE and SE. In our work, we discover some interesting and novel property-preserving transformation techniques that enable generic construction of an SE scheme from an HIPE scheme, and vice versa.